DSSCs based on unsymmetrical A3B type Zn(II) and TiO(IV) naphthalenephthalocyanine/porphyrin cocktail dyes: A potential alternative for ruthenium based sensitizers - Demirci, Yiğit Can; Çakar, Soner; Sevim, Altuğ Mert; Gül, Ahmet; Özacar, Mahmut (Elsevier BV, 2023)
To increase the efficiency of dye-sensitized solar cells (DSSCs), there is still a need for alternative dyes that can absorb a broad spectrum of sunlight and maintain high conversion efficiencies. In order to meet these requirements, a cocktail dye made up of novel phthalocyanines together with a porphyrin have been designed. The novel unsymmetrical phthalocyanines are two ferrocenylphenoxy-naphthalenephthalocyanine (FPNPc) with Zn (ZnFPNPc) or TiO (TiOFPNPc) at the inner core and 4-ferrocenylphenoxy and 4-carboxybenzo substituents at peripheral positions. In order to increase their UV-Vis absorption capacity, cocktails have been prepared with the synthesized new dyes (ZnFPNPc or TiOFPNPc) and YD2 porphyrin dye. The full characterization of novel synthesized dyes has been performed by UV-Vis absorption, FTIR, H1-NMR, MALDI-TOF, electrochemical, TD-DFT techniques. In this work we have prepared DSSCs based on YD2 and phthalocyanine dye molecule with different cocktail ratio (YD2 + ZnFPNPc or YD2 + TiOFPNPc ratios: 1:1, 1:2, 2:1, 1:3, 3:1, 1:4 and 4:1). The best solar cell performance has been performed in the cases of YD2 + ZnFPNPc (3:1) (9.96%) and YD2 + TiOFPNPc (3:1) (10.72%) cocktail dyes. Due to the high efficiency values obtained, these new cocktail dyes are expected to be a good alternative to the ruthenium-based complex dyes used in DSSCs and pave the way for potential alternative dyes.
Keywords: Phthalocyanines; Porphyrins; Cocktail dyes; Metal complexes dyes; Dye-sensitized solar cells (DSSC); Solar energy; Density-functional theory